A Hemichorea and Hemiplegy as a Clinical Manifestation of Acute Ischemic Stroke - Shahab, Fatimah; Hunaifi, Ilsa; Subagiartha, I Wayan (Faculty of Medicine Universitas Mataram, 2020)
Hemichorea / hemibalismus (HCHB) and other hyperkinetic movement disorders are a rare presentation of stroke, usually secondary to deep infarctions affecting the basal ganglia and the thalamus. This case report aims to describe patients who experience HCHB as early symptoms of acute stroke infarction accompanied by hyperglycemia. In this case the complaint was accompanied by facial and hypoglossus nerve paresis, and hemiplegic of the contralateral limb of the lesion. Serum glucose and HBA1C levels are elevated. CT scan image shows an infarction in the basal ganglia. The combination of new striatal lesions and hyperglycemia can induce HCHB because both of these can lead to increased inhibition of the subtalamic nucleus and disruption of thalamus GABAergic inhibition. Key words: Hemibalismus, hemichorea, hyperglycemia, ischemic stroke